Determining the biocontrol capacities of Trichoderma spp. originating from Turkey on Fusarium culmorum by transcriptional and antagonistic analyses - Sefer, Özlem; Özsoy, Esma; Yörük, Emre; Özkale, Evrim (Frontiers in Fungal Biology, 2023)
In this study aiming to investigate potential fungal biocontrol agents for Fusarium culmorum, several isolates of Trichoderma spp. were evaluated for their antagonistic effects by means of transcriptional analyses. At first, 21 monosporic Trichoderma spp. isolates were obtained from natural wood debris and wood area soils in Manisa, Turkey. Trichoderma spp. Isolates were identified as belonging to four different species (T. atroviride, T. harzianum, T. koningii, and T. brevicompactum) by tef1-α sequencing. Then, the linear growth rate (LGR) of each species was calculated and determined to be in a range between 13.22 ± 0.71 mm/day (T. atroviride TR2) and 25.06 ± 1.45 mm/day (T. harzianum K30). Inter-simple sequence repeat (ISSR) genotyping validated the tef1-α sequencing results by presenting two sub-clusters in the dendrogram. We determined the genetically most similar (TR1 & TR2; 97.77%) and dissimilar (K9 & K17; 40.40%) individuals belonging to the same and different species, respectively. Dual sandwich culture tests (which are useful for antagonism studies) revealed that T. harzianum K21 (the least suppressive) and T. brevicompactum K26 (the most suppressive) isolates suppressed F. culmorum with growth rates of 3% and 46%, respectively. Expressions of genes previously associated with mycoparasitism-plant protection-secondary metabolism (nag1, tgf-1, and tmk-1) were tested by quantitative real-time polymerase chain reaction (qRT-PCR) in both those isolates. While there were no significant differences (p>0.05) in expression that were present in the K21 isolate, those three genes were upregulated with fold change values of 2.69 ± 0.26 (p<0.001), 2.23 ± 0.16 (p<0.001), and 5.38 ± 2.01 (p<0.05) in K26, meaning that the presence of significant alteration in the physiological processes of the fungus. Also, its mycoparasitism potential was tested on Triticum aestivum L. cv Basribey in planta, which was infected with the F. culmorum FcUK99 strain. Results of the trials, including specific plant growth parameters (weight or length of plantlets), confirmed the mycoparasitic potential of the isolate. It can be concluded that (i) nag1, tgf-1, and tmk-1 genes could be approved as reliable markers for evaluation of BCA capacities of Trichoderma spp. and (ii) the T. brevicompactum K26 strain can be suggested as a promising candidate for combating in F. culmorum diseases following the necessary procedures to ensure it is non-hazardous and safe.